The Influence of Organizational Culture and Organizational Climate on Employee Productivity at PT. Rajawali Nusindo Medan Branch - Manalu, Juita; Sitanggang, HD. Melva; Bachtiar, Lasman Eddy (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research was conducted to determine Organizational Culture and Organizational Climate on Work Productivity, this research uses quantitative methods with an associative approach. In this study the population of employees working at PT. Rajawali Nusindo Medan Branch. The sampling method in this study used a non-probability sampling technique with a saturated sampling approach of 28 respondents. Data analysis techniques used validity test, reliability test, classic assumption test, multiple linear regression analysis, t-test, F test, and coefficient of determination (R2) using the SPSS version 21 application. The results of the t-test for the organizational culture variable are t count 2.161 > t table of 2.059 meaning that organizational culture affects work productivity and organizational climate variable t count is 3.428 > 2.059 meaning organizational climate affects work productivity. F test of organizational culture variable and organizational climate variable F count of 7.856 > F table 3.39 shows that organizational culture and organizational climate jointly affect work productivity.